Heparanase 1 Upregulation Promotes Tumor Progression and Is a Predictor of Low Survival for Oral Cancer - Rodrigues, André A. Nimtz; Lopes-Santos, Lucilene; Lacerda, Pammela A.; Juste, Mariana F.; Mariz, Bruno Augusto; Cajazeiro, Débora C.; Giacobbe, Victoria; Borges, Rafael; Casarim, André; Callegari, Giovanna De Sanctis; Claret Arcadipane, Fernando Antônio M.; Aprahamian, Ivan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Oral cavity cancer is still an important public health problem throughout the world. Oral squamous cell carcinomas (OSCCs) can be quite aggressive and metastatic, with a low survival rate and poor prognosis. However, this is usually related to the clinical stage and histological grade, and molecular prognostic markers for clinical practice are yet to be defined. Heparanase (HPSE1) is an endoglycosidase associated with extracellular matrix remodeling, and although involved in several malignancies, the clinical implications of HPSE1 expression in OSCCs are still unknown. Methods: We sought to investigate HPSE1 expression in a series of primary OSCCs and further explore whether its overexpression plays a relevant role in OSCC tumorigenesis. mRNA and protein expression analyses were performed in OSCC tissue samples and cell lines. A loss-of-function strategy using shRNA and a gain-of-function strategy using an ORF vector targeting HPSE1 were employed to investigate the endogenous modulation of HPSE1 and its effects on proliferation, apoptosis, adhesion, epithelial–mesenchymal transition (EMT), angiogenesis, migration, and invasion of oral cancer in vitro. Results: We demonstrated that HPSE1 is frequently upregulated in OSCC samples and cell lines and is an unfavorable prognostic indicator of disease-specific survival when combined with advanced pT stages. Moreover, abrogation of HPSE1 in OSCC cells significantly promoted apoptosis and inhibited proliferation, migration, invasion, and epithelial–mesenchymal transition by significantly decreasing the expression of N-cadherin and vimentin. Furthermore, a conditioned medium of HPSE1-downregulated cells resulted in reduced vascular endothelial growth. Conclusion: Our results confirm the overexpression of HPSE1 in OSCCs, suggest that HPSE1 expression correlates with disease progression as it is associated with several important biological processes for oral tumorigenesis, and can be managed as a prognostic marker for patients with OSCC.